Research on Security Algorithm for Crossing Heterogeneous Network Based on Unified Communication Technology - Yingying Chen; Geng Zhang; Mingyue Di; Jie Li; Meilin Dang; Guilan Xing (Dianxin kexue)
Due to the unified protocol specification, encryption, and firewalls and other security measures at present, communication within the network environment are in good usability and security in heterogeneous network environment. However, in order to guarantee the availability, safety of the communication between heterogeneous networks has been reduced. Based on the study of heterogeneous networks through the issues and the status quo on the symmetric key cryptography, asymmetric key cryptosystem in-depth research, an encryption algorithm based on the RSA algorithm and improved DES algorithm was proposed. Finally, the use of case study shows that the algorithm has good security.